PERTUMBUHAN TANAMAN KANTONG SEMAR (Nepenthes rafflesiana Jack.) DENGAN MODIFIKASI KONSENTRASI MEDIA DAN pH SECARA IN VITRO - Lea Yony Kunita; Susiyanti .; Sulastri Isminingsih; Yupi Isnaini (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2011)
This research about growth of pichter plant Nepenthes rafflesiana Jack was aimed to determine the modification medium’s concentration and pH at in vitro . This research has been conducted in the laboratory of plant concervation center Bogor Botanical Garden. This research was doing from Juni to September 2010. research using randomized block design with 2 factor, the first factor is modification concentration medium MS, consisting of 5 level is 1 MS, 1/2 MS, 1/4 MS, 1/8 MS, dan 1/16 MS; and the second factor is the pH medium was consisted 3 level: pH 4,7, pH 5,7 dan pH 6,7 was repeated four times. The results showed that concentration medium 1/8 MS and all pH medium were significant the variable of number pichter, number rootlet, percentage of planlet life, percentage of planlet pichter, percentage of planlet rootlet.Key words: Nepenthes rafflesiana Jack, medium concentration, pH.